Auditory temporal processing and its disorders - Eggermont, Jos J. (Oxford University Press, 2015)
"'Auditory temporal processing' determines our understanding of speech, our appreciation of music, our ability to localize a sound source--even to listen to a person in a noisy crowd ... Auditory Temporal Processing and its Disorders reviews comprehensively the mechanisms for temporal processing in the auditory system, looking at how these underlie specific clinical disorders, with implications for their treatment. Written by a prolific researcher in auditory neuroscience, this book is valuable for auditory neuro-scientists, audiologist, neurologists, and speech language pathologists"--Page 4 of cover.